Predictors of Online Learning Readiness and Their Consequences on Learning Engagement and Perceived Teaching Quality during Covid19 - Mikail Ibrahim; Saleh Hamood Nasser AL-Sinawi; Suo Yan ju; Mohammed Borhandden Musah (Sciedu Press, 2024)
This empirical study attempts to investigate the causal relationships between the predictors of online learning readiness and its effects on learning engagement and perceived teaching quality. In other words, the study aims to explore the direct relationship between goal orientation and perceived teaching quality, on the one hand, and the students’ learning engagement and perceived teaching quality and their indirect relationships via online learning readiness. A total of 703 students from Malaysian and Omani higher institutions voluntarily participated in this study following the quota sampling technique. Structural Equation Modeling (SEM) was used to analyze the data gathered. The results of the analysis suggested that the goal orientation and perceived self-efficacy were statistically and directly related to learning engagement and perceived teaching quality and indirectly via online learning readiness.